The Effect of Corporate Shared Value (CSV) of Halal Agroindustry on PT. Great Giant Pineapple (GGP) on the Welfare of Partner Farmers (E-Grower) - Fauzi Fauzi; Laksamana Bangsawan; Sri Surya Mandala; Kasmi Kasmi (International Journal of Ecma Science, 2021)
This study aims to determine the Effect of Corporate Shared Value (CSV) in Halal Agroindustry at PT. Great Giant Pineapple (GGP) towards the welfare of partner farmers (E-Growers) in Tanggamus Regency. The research method used is quantitative research. Respondent data was collected using a questionnaire distributed to GGP partner farmers. A sample of 206 respondents was analyzed using simple linear regression analysis. The researcher found that the positive effect of CSV was 19.5% and had a fairly strong correlation value on the Welfare of Partner Farmers (E-Growers) in Tanggamus Regency. The Regional Government and GGP can continue to support efforts to develop SCV for the welfare of the community with various policies and training for empowering human resources and nursery capital.